Adenosine diphosphate and the measurement of platelet adhesiveness - Bloom, A. L. (1967)
Platelet adhesiveness to glass beads was measured in citrated blood at intervals up to two hours after the addition of adenosine diphosphate (A.D.P.). Adhesiveness increased for 15 minutes, fell towards the original level, and then steadily increased. The initial changes were associated with the formation and subsequent dispersal of platelet clumps. The sequence of events resembled the reported platelet aggregation, the disaggregation and secondary aggregation effect of A.D.P. and emphasizes the importance of a standard technique in the measurement of A.D.P.-induced platelet adhesiveness.